RACIAL DISCRIMINATION TOWARDS AFRICAN-AMERICAN IN LANGSTON HUGHES’S SELECTED POEMS - Tarukallo Wilson; Nasrullah Nasrullah; Jonathan Irene Sartika Dewi Max (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni dan Budaya, 2022)
This study analyzes three poems written by Langston Hughes entitled As I Grew Older, Dinner guest; me and I Dream a World poems. Being an African- American author who experiences many discrimination in his life, he illustrates or recounts about the case of racial discrimination clearly in his many works. Langston Hughes’s works tell us about slavery and inequality between African-American and White-American, he does not only try to make the works that criticize the phenomenon of African-American people who suffer from suppression, racial separation but also describes his hopes and dreams to be free and equal like White-American. The aim of this study, first, is to find out racial discrimination described by Langston Hughes which is reflected on his poems and second, is to reveal how is poet’s life when he was experiencing discrimination by analysing his poems. In answering the research questions, the researcher uses a discrimination theory by Sergio Romero and several theories such as, the element of poetry which is applied to describe the racial discrimination happened in poems; and the theories of socio-cultural historical approach and Jim Crow Law on racial discrimination which are applied to reveal how the racial discrimination experienced by Langston Hughes is reflected in his As I Grew Older, Dinner guest; me and I Dream a World poems. Based on the analysis, the findings revealed out that racial discrimination described in Hughes’s poems is real. Through Hughes’s poems, the researcher knows that African-American got bad treatments such as; being considered as second citizen in society, mistreated at the table dinner, treating as non-equal in society. Hughes tries to tell his experiences of being threatened due to his racial ethnicity by writing poems and this is clearly revealed to the reader throughout his poems.